Persepsi Guru dan Orang Tua tentang Pendidikan Seks di SD Chalidana Islamic School Menganti - Susi Ayun Nuryani; Imam Bahrozi; Ivo Yuliana (Jurnal Inovasi Pembelajaran dan Pendidikan, 2025)
Indonesia faces a pressing educational challenge related to sex, with many teenagers becoming pregnant out of wedlock due to negligent parental supervision. Given this fact, sex education is essential to prevent or mitigate this. However, perceptions of sex education remain negative while sex education should be provided to children as soon as possible by teachers and parents. Most research on perceptions of sex education focuses on teachers or parents alone. However, this study aims to determine the perceptions of both teachers and parents regarding the implementation and strategies for implementing sex education through boy and girl activities, as well as the roles of teachers and parents in providing sex education to children at ES of CIS Menganti. This study used a qualitative-descriptive method with data collection techniques through observation, interviews, and documentation. The results show that teachers and the majority of parents (83.3%) have positive perceptions of sex education, packaged in the Boys Talk and Girls Talk programs; the implementation of it in this school is carried out routinely with an approach appropriate to the age and needs of students; teachers and parents play a crucial role in providing sex education to children to prepare them for puberty and adulthood.